2016
DOI: 10.1021/acs.est.6b02084
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Rare Earth Elements and Yttrium from Passive-Remediation Systems of Acid Mine Drainage

Abstract: Rare earth elements and yttrium (REY) are raw materials of increasing importance for modern technologies, and finding new sources has become a pressing need. Acid mine drainage (AMD) is commonly considered an environmental pollution issue. However, REY concentrations in AMD can be several orders of magnitude higher than in naturally occurring water bodies. With respect to shale standards, the REY distribution pattern in AMD is enriched in intermediate and valuable REY, such as Tb and Dy. The objective of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(145 citation statements)
references
References 52 publications
(102 reference statements)
11
119
0
3
Order By: Relevance
“…power generation, X-ray imaging, fibre 36 optics, among others) [2]. Although REEs are found in a minor proportion compared to the above-mentioned 37 transition metals, their concentration is relatively high (two orders of magnitude higher than the one presented in 38 natural waters) [3,4]. One of the largest sulphide ore deposits in the world is located in the Iberian Pyrite Bell 39 (IPB), which is situated in the Southern Iberian Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…power generation, X-ray imaging, fibre 36 optics, among others) [2]. Although REEs are found in a minor proportion compared to the above-mentioned 37 transition metals, their concentration is relatively high (two orders of magnitude higher than the one presented in 38 natural waters) [3,4]. One of the largest sulphide ore deposits in the world is located in the Iberian Pyrite Bell 39 (IPB), which is situated in the Southern Iberian Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…, which is several orders of magnitude higher than in naturally occurring water bodies (Stewart et al 2017;Ayora et al 2016;Merten et al 2005). …”
Section: Opportunities Of Resource Recovery From Amdmentioning
confidence: 82%
“…A strong association between high REE concentrations and acidity has been described in surface and ground water (Welch et al 2009;Noack, Dzombak & Karamalidis 2014). Recently, Ayora et al 2016 reported that REY content in AMD can be several orders of magnitude higher than in naturally occurring water bodies.…”
Section: Opportunities Of Resource Recovery From Amdmentioning
confidence: 99%
See 2 more Smart Citations